Training and Incorporating Students in SARS-CoV-2 Case Investigations and Contact Tracing. (March 2021) - Pogreba Brown, Kristen; Austhof, Erika; Rosa Hernández, Ayeisha M.; McFadden, Caitlyn; Boyd, Kylie; Sharma, Jayati; Battaglia, Sarah; Shilen, Alexandra; Heslin, Kelly M.
Objectives: In June 2020, Arizona had the fastest-growing number of cases of coronavirus disease 2019 (COVID-19) worldwide. As part of the growing public health response, the University of Arizona Student Aid for Field Epidemiology Response (SAFER) team was able to modify and increase case investigation efforts to assist local health departments. We outline the recommended logistical and management steps to include students in a public health response of this scope. Methods: From April 1 through September 1, 2020, the SAFER team identified key components of a successful student team response: volunteer training, management that allows more senior students to manage newer students, adoption of case-management software, and use of an online survey platform for students to conduct interviews consistently and allow for data quality control and management. Results: From April 1 through September 1, 2020, SAFER worked with 3 local health departments to complete 1910 COVID-19 case investigations through a virtual call center. A total of 233 volunteers and 46 hourly student workers and staff members were involved. As of September 2020, students were completing >150 interviews per week, including contact-tracing efforts. Practice Implications: Developing relationships between applied public health and academic programs can relieve the burden of low-risk, high-volume case investigations at local and state health departments. Furthermore, by establishing a virtual call center, health sciences faculty and students can volunteer remotely during a pandemic with no additional risk of infection.